Transient Osteoporosis of Pregnancy of the Bilateral Hips in Twin Gestation: A Case Series. Issue 1 (8th August 2014) - Reese, Maria E.; Fitzgerald, Colleen; Hynes, Christina
Abstract: Transient osteoporosis of pregnancy has been described as a rare, self‐limiting disease of unclear etiology that presents as severe pain, which typically affects pregnant women in their third trimester. We describe 3 cases of primigravid pregnant women with twin gestation who reported unilateral hip pain and who were diagnosed with transient osteoporosis of pregnancy of the hip by magnetic resonance imaging. These women were advised to undergo limited weight bearing and activity modification to minimize the risk of fracture. Each patient was able to proceed through her pregnancy, delivery, and postpartum course without complication, with symptom resolution, and return to unrestricted activity.